Measurement of 43Sc and 44Sc production cross-section with an 18 MeV medical PET cyclotron. (November 2017) - Carzaniga, Tommaso Stefano; Auger, Martin; Braccini, Saverio; Bunka, Maruta; Ereditato, Antonio; Nesteruk, Konrad Pawel; Scampoli, Paola; Türler, Andreas; van der Meulen, Nicholas
Abstract: 43 Sc and 44 Sc are positron emitter radionuclides that, in conjunction with the β − emitter 47 Sc, represent one of the most promising possibilities for theranostics in nuclear medicine. Their availability in suitable quantity and quality for medical applications is an open issue and their production with medical cyclotrons represents a scientific and technological challenge. For this purpose, an accurate knowledge of the production cross sections is mandatory. In this paper, we report on the cross section measurement of the reactions 43 Ca(p, n) 43 Sc, 44 Ca(p, 2n) 43 Sc, 46 Ti(p, α ) 43 Sc, and 44 Ca(p, n) 44 Sc at the Bern University Hospital cyclotron. A study of the production yield and purity performed by using commercially available enriched target materials is also presented. Abstract : Highlights: The production cross sections of Sc-43 and Sc-44 by proton irradiation were measured. The thick target production yields and purities were evaluated. Method based on irradiating the whole target by constant surface density proton beam. Measurements performed using a beam transfer line and a 18 MeV medical PET cyclotron.